Forearm Volume Changes Estimated by Photo-Plethysmography During an Original Candlestick/Prayer Maneuver in Patients With Suspected Thoracic Outlet Syndrome - Hersant, Jeanne; Ramondou, Pierre; Chavignier, Victoire; Chavanon, Axelle; Feuilloy, Mathieu; Picquet, Jean; Henni, Samir; Abraham, Pierre (Frontiers in Physiology, 2021)
Objective: Hemodynamic investigations in thoracic outlet syndrome (TOS) remain difficult, even in trained hands. Results are generally reported as either presence or absence of venous compression. In fact, in patients with suspected TOS but without chronic venous occlusion, the forearm volume changes may result from various combinations of: forearm position from heart level, arterial inflow and/or venous outflow positional impairment. Design: Cross sectional, retrospective, single center study, accessible on Clinicaltrial.gov under reference NCT04376177. Material: We used venous photo-plethysmography (V-PPG) in 151 patients with suspected TOS. Subjects elevated their arms to the “candlestick” (Ca) position for 30 seconds and then kept their arm elevated in front of the body for an additional 15 secs (“prayer” position; Pra). This CA-Pra procedure was repeated three times by each patient with recording of both arms. Method: We classified V-PPG recordings using an automatic clustering method. Result: The blinded clustering classification of 893 V-PPG recordings (13 missing files) resulted in four out of seven clusters, allowing the classification of more than 99% of the available recordings. Each cluster included 65.73%, 6.16%, 17.13% 10.8 % of the recordings, respectively. Conclusion: Venous hemodynamic profiles in TOS are not only either normal or abnormal. With V-PPG, four clusters were observed consistent with, and assumed to result from, the four possible associations of presence/absence of arterial inflow/venous outflow positional impairment: 1/ Normal response (maximal emptying in Ca & Pra); 2/ isolated inflow impairment (emptying in Ca and filling in Pra due to post ischemic vasodilation); 3/ isolated venous outflow impairment (emptying then filling in Ca due to arterial inflow and emptying in Pra); 4/ simultaneous inflow/outflow impairment (emptying in Ca but no filling due to concomitant inflow impairment and further emptying in Pra).